Helping Families and Communities Recover From Disaster: Lessons Learned From Hurricane Katrina and Its Aftermath.
DOI: 10.1037/12054-002
|View full text |Cite
|
Sign up to set email alerts
|

The caregiver-child relationship and children's adjustment following Hurricane Katrina.

Abstract: During and following Hurricane Katrina, families and children in the central Gulf Coast experienced multiple losses, forced relocation, unsafe living conditions, violence, and deprivation (see Introduction and chaps. 1 and 10, this volume). Indeed, in the days and weeks following the floods, many children and their families were exposed to violence, did not know the whereabouts of their loved ones, and were unable to meet their basic needs (Osofsky, Osofsky, &. Harris, 2007). Entire communities and social ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Interparental conflict has been connected to post-disaster posttraumatic stress symptoms in children (Wasserstein & La Greca, 1998). Caregiver-child conflict, caregiver unavailability to talk about the hurricane, and children’s perceptions of caregiver’s hurricane-related distress, was related to children’s post-disaster traumatic stress symptoms beyond what was explained by hurricane exposure alone (Gil-Rivas, Kilmer, Hypes, & Roof, 2010). However, in another study of parent-child factors affecting MH in Hurricane Katrina survivors, parenting behaviors did not add to the variance accounted for above and beyond hurricane exposure amongst those displaced after the storm (Kelley et al, 2010).…”
Section: Family Influences On Children’s Post-disaster Mental Healthmentioning
confidence: 99%
“…Interparental conflict has been connected to post-disaster posttraumatic stress symptoms in children (Wasserstein & La Greca, 1998). Caregiver-child conflict, caregiver unavailability to talk about the hurricane, and children’s perceptions of caregiver’s hurricane-related distress, was related to children’s post-disaster traumatic stress symptoms beyond what was explained by hurricane exposure alone (Gil-Rivas, Kilmer, Hypes, & Roof, 2010). However, in another study of parent-child factors affecting MH in Hurricane Katrina survivors, parenting behaviors did not add to the variance accounted for above and beyond hurricane exposure amongst those displaced after the storm (Kelley et al, 2010).…”
Section: Family Influences On Children’s Post-disaster Mental Healthmentioning
confidence: 99%
“…The present study grows out of a larger project assessing children and caregivers post-Hurricane Katrina. In describing the sample’s experiences, Gil-Rivas et al (2010) noted that all participating caregivers and 86.8% of their children endorsed experiencing at least one hurricane-related traumatic event, and 63.2% of children reported that Hurricane Katrina was one of the “most scary” events they had experienced. Overall, children reported experiencing considerable adversity and, one year post-hurricane Katrina, 21% of the children obtained posttraumatic stress symptom (PTSS) scores suggesting the presence of a probable Posttraumatic Stress Disorder diagnosis, and nearly all reported experiencing at least one PTSS much or most of the time during the previous month (Gil-Rivas et al, 2010).…”
Section: The Present Study: Context and Aimsmentioning
confidence: 99%
“…Overall, children and families affected by Katrina faced multiple adversities in the short-and long-term aftermath (see, e.g., Gil-Rivas, Kilmer, Hypes, & Roof, 2010; Osofsky, Osofsky, Kronenberg, & Cross Hansel, 2010). Although these issues did not start with Katrina, families’ capacity for coping and response was diminished, resources (both financial and psychological) were taxed, and ongoing issues were exacerbated.…”
mentioning
confidence: 99%
“…For example, parents and children may avoid talking about the experience for fear of upsetting each other. One year after Hurricane Katrina, children who perceived their caregivers as unwilling or as being too upset to talk reported higher levels of posttraumatic stress symptoms (Gil-Rivas et al, 2010). In a study of families indirectly exposed to the September 11th attacks (Gil-Rivas, Silver, Holman, McIntosh, & Poulin, 2007), higher posttraumatic stress symptoms were reported by adolescents who chose not to talk about the event because they did not want to upset their parents and/or doubted that talking would help.…”
Section: Changes In the Dynamics And Structure Of Social Relationshipsmentioning
confidence: 99%
“…There is strong consensus that postdisaster family functioning is an important factor explaining variability in the psychological distress of their members. Across numerous studies using a variety of samples, measurement strategies, and methodologies, increased levels of postdisaster parental symptoms have been associated with higher levels of symptoms in children (e.g., Gil-Rivas, Kilmer, Hypes, & Roof, 2010;Green et al, 1991;Kiliç, Ö zgüven, & Sayil, 2003;McFarlane, 1987b;McLaughlin et al, 2009;Proctor et al, 2007;Scheeringa & Zeanah, 2008;Spell et al, 2008;Swenson et al, 1996). This association is not surprising, in that parents are a primary source of social support for children and adolescents (Cauce, Reid, Landesman, & Gonzalez, 1990) and also the primary source of coping assistance for children in the aftermath of disasters .…”
Section: Changes In the Dynamics And Structure Of Social Relationshipsmentioning
confidence: 99%